1990
DOI: 10.1007/bf00998161
|View full text |Cite
|
Sign up to set email alerts
|

123I-MIBG pulmonary removal: a biochemical marker of minimal lung endothelial cell lesions

Abstract: Circulating biogenic amines, such as serotonin or norepinephrine, are cleared by the lung and can be considered as indicators of pulmonary endothelial integrity. An iodinated norepinephrine analogue, metaiodobenzylguanidine (MIBG), is extracted in the lung by an active, saturable transport system. In order to investigate the use of MIBG lung extraction to detect minimal lung endothelial cell lesions, an experimental model of initial pulmonary vascular lesions was developed in rats using repeated daily intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 16 publications
0
32
0
1
Order By: Relevance
“…AECs in the lung microvasculature have the metabolic function of circulating vasoactive norepinephrine (12)(13)(14)(15). 123 I-metaiodobenzylguanidine ( 123 I-MIBG) shares the same uptake as norepinephrine in AECs (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…AECs in the lung microvasculature have the metabolic function of circulating vasoactive norepinephrine (12)(13)(14)(15). 123 I-metaiodobenzylguanidine ( 123 I-MIBG) shares the same uptake as norepinephrine in AECs (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Previous studies reported that reduced lung uptake of 123 I-MIBG correlated with pulmonary endothelial dysfunction in animals and humans. [16][17][18][19] Therefore, Kruskal-Wallis ANOVA showed significant differences in the myocardial uptake of 123 I-MIBG in the early phase, uptake of 123 I-MIBG in the delayed phase, and washout rate of 123 I-MIBG among controls, patients with CTEPH, and patients with PAH. Steel-Dwass analysis showed significant differences in the myocardial uptake of 123 I-MIBG in the early phase between controls and patients with CTEPH (* 1 P = 0.0094) or patients with PAH (* 2 P = 0.0030).…”
Section: Discussionmentioning
confidence: 99%
“…14) In cardiology, 123 I-MIBG is utilized to evaluate the cardiac sympathetic status, arrhythmia risk, and prognosis of patients with heart failure. 15) Slosman, et al [16][17][18] demonstrated that like norepinephrine, 123 I-MIBG was taken up and metabolized by the pulmonary endothelium in sheep and rat lungs. Furthermore, they analyzed 123 I-MIBG extraction in human lungs and suggested that 123 I-MIBG extraction might be a valuable tool for evaluating early metabolic changes that most likely reflect the pulmonary vascular endothelial function.…”
mentioning
confidence: 99%
“…It is well known that transport of these biogenic amines requires normal endothelial cell integrity. Thus, 123 I-MIBG is regarded as an indicator of pulmonary endothelial function [6][7][8][9] , because it behaves in a quantitatively similar manner to norepinephrine in pulmonary circulation 10,11 . Slosman et al initially evaluated lung uptake of MIBG using animal models and demonstrated decreased MIBG lung extraction in bleomycin 9 -and endotoxin 12 induced endothelial injury.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 123 I-MIBG is regarded as an indicator of pulmonary endothelial function [6][7][8][9] , because it behaves in a quantitatively similar manner to norepinephrine in pulmonary circulation 10,11 . Slosman et al initially evaluated lung uptake of MIBG using animal models and demonstrated decreased MIBG lung extraction in bleomycin 9 -and endotoxin 12 induced endothelial injury. Recently, several clinical studies using this property of 123 I-MIBG scintigraphy, showed that decreased 123 I-MIBG kinetic in lung could serve as a novel diagnostic tool to evaluate the endothelial damage in patients with pulmonary fibrosis 13 and myeloperoxidase antineutrophil cytoplasmic antibodies positive vascultis 14 .…”
Section: Introductionmentioning
confidence: 99%